Pregnancy problems: a case report - Findlay, Nicholas (International Surgery Journal, 2025)
Appendicitis is a common surgical cause of abdominal pain. Investigation and diagnosis of the cause of right lower quadrant abdominal pain is more complex in women who are pregnant. A 27 year old, 34 week pregnant female presented with migratory RIF pain. Inflammatory markers were mildly elevated. There was a strong patient preference to avoid unnecessary. In this case we demonstrate the importance of keeping a broad differential diagnosis despite imaging findings. With a higher index of suspicion in this case surgery could potentially have been avoided. This could have avoided potential morbidity and additional psychosocial stress during the patient’s pregnancy. As such the limitations of diagnostic certainty with imaging especially less common modalities such as MRI should be appreciated.